Meningkatkan Perkembangan Sosial Emosional Anak Melalui Permainan Budaya Lokal Mak-Mak Ambo - Erleni, Erleni; Haryono, Mimpira; Sari, Rika Partika (Journal Of Dehasen Educational Review, 2022)
The purpose of this study was to improve the social emotional development of children in group B through the local cultural game mak-mak ambo at the CEMPAKA PAUD Unit, Gunung Egypt Village, Semidang Alas Maras District, Seluma Regency. Classroom Action Research (PTK) which is focused on classroom situations, or commonly known as classroom action research, the procedure used is in the form of a cycle. The main subjects in this study were 15 children in group B. This Classroom Action Research uses the John Elliot model where each cycle consists of four main activities, namely planning, implementing, observing, and reflecting which are carried out through two cycles, namely cycles I and II, each cycle consisting of one meeting. Data collection techniques using observation and documentation methods. Data analysis was carried out in a qualitative-quantitative descriptive manner with the emphasis being used to determine process improvements expressed in a predicate, while quantitative data analysis was used to determine yield improvements using percentages. The results of increasing children's social emotional development through the local cultural game mak-mambo in the CEMPAKA Early Childhood Education Unit, Seluma Regency, in the first cycle of the first meeting was 74% and in the second cycle of the first meeting there was an increase of 90%. The conclusion of the study that through local cultural games mak-mambo can improve social emotional development in group B children in the CEMPAKA Early Childhood Education Unit, Seluma Regency, it is proven that in cycle II there was a significant increase, the percentage of achievement was 90% with very good development criteria (BSB).